Speed Test and Measurement Tools Shooting Sensor Based - Yoepiter Zega; Amir Supriadi; Novita Novita (UNIB Press, 2022)
Tool and test and measurement of shooting sensor-basedThis research was carried out on athletes from Darul Ulum Fc and Bangsal FC in May 2022. This type of research is a development research with a Research and Development (R&D) from Sugiyono. This research was conducted with this research carried out with 9 stages (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing and (9) Final product. The population in this study used athletes from Darul Ulum FA and Bangsal FC. The sampling technique used purposive sampling with the first phase of the trial, which consisted of 15 athletes from Darul Ulum FC and the second phase of the trial, which consisted of 17 Bangsal FC athletes. Furthermore, from the first stage of the trial, which amounted to 15 people, the figure was 93.16% with the Very Eligible criteria, then from the second stage of the trial which amounted to 17 athletes, the figure was 93.52% in the Very Eligible category. Based on the data obtained, the development of a shooting speed measurement tool is declared feasible to be developed as a sensor-based test and shooting.